EKSISTENSI TARI POH KIPAH PADA MASYARAKAT LHOKSEUMAWE - Niza Vayatul Niza; Yusnizar Heniwaty (Gesture: Jurnal Seni Tari, 2018)
ABSTRACT This study is a study of the existence of Poh Kipah dance in Lhokseumawe community. In this discussion using the theories relating to the topic of research is the theory of existence.The method used in this research is qualitative research method. The population in this study as well as a research sample of artists and dancers. Data collection techniques include literature study, interview, observation, and documentation.Based on the research that has been done, the existence of Poh Kipah dance which is seen from three time span, first from 1959-1979, Poh Kipah dance at this time become the beginning of the show performed as entertainment on the implementation to commemorate the Prophet's Maulid and the Circumcision. Where in the past this dance only has some movements such as hitting the fan into the palm of the hand, tapping the fan handle to the floor palm. Music accompaniment using internal music in the form of poetry in chant by syeh and in addition to the fan tap. The pattern of the floor from the beginning of entry has been sitting on the stage, with male dancers who numbered eight or the whole peoples, the clothing was only wearing bay clothing and wearing a cap, where in the dance held in the field and on the yard of the mosque, the purpose of dance Inn as an entertainment event at the Prophet's Maulid event. Second from 1979-1999, Poh Kipah dance in this period nothing changed from its existence in because at this time there is no data or documents that are clear for this dance performance. Third 1999-present, in this period the existence of this dance has undergone several changes that can be seen from the addition of varied motion, the music has been changed with the addition of musical instruments serune kale and rapai, in the composition of the accompaniment, from the side of the dancer has included a female dancer In the composition of the dance, this event is still still encountered in the entertainment event Prophet's Maulid and Circumcision but now we have found also in festivals, and Culture Week of Aceh. Keywords: Existence, Poh Kipah Dance In Lhokseumawe Society.